Cultural Tourism Branding in Kuta Traditional Village, Ciamis - West Java - Aat Ruchiat Nugraha; Diah Fatma Sjoraida; Iriana Bakti; Dian Wardiana Sjuchro (Ikatan Sarjana Komunikasi Indonesia, 2025)
The Kuta Ciamis Traditional Village is one of the Sundanese indigenous communities that still preserves its ancestral heritage. The existence of the Kuta Traditional Village to this day is inseparable from the combination of natural beauty, traditional cultural heritage, and mystical aura maintained by the local residents from generation to generation. Located on the border of West Java and Central Java, the uniqueness and local wisdom found in Kuta Village are the main elements in forming a strong and attractive branding for tourists. This study aims to determine and explain how the branding process of Kuta Traditional Village as one of the cultural tourism destinations based on local wisdom in West Java was formed. The research method was carried out qualitatively by collecting data through observations about the lives of indigenous residents and the existence of traditional institutions, interviews with traditional leaders and literature studies from documents, books, journals and other relevant references about indigenous communities. The results of the study indicate that the branding of the